2022
DOI: 10.1038/s41598-022-21563-z
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of soil fauna functional groups and their estimated litter consumption across biomes

Abstract: Soil invertebrates (i.e., soil fauna) are important drivers of many key processes in soils including soil aggregate formation, water retention, and soil organic matter transformation. Many soil fauna groups directly or indirectly participate in litter consumption. However, the quantity of litter consumed by major faunal groups across biomes remains unknown. To estimate this quantity, we reviewed > 1000 observations from 70 studies that determined the biomass of soil fauna across various biomes and 200 obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 98 publications
1
14
0
1
Order By: Relevance
“…In another strong contrast to the first global model of PREDICTS data, soil organisms in pasture attain similar taxon richness and abundance as in primary vegetation. This agrees with other studies that found high soil fauna biomass in temperate grasslands (Heděnec et al, 2022). Pastoral management practices cause less physical disruption of the soil structure than many arable farming practices (Aksoy et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In another strong contrast to the first global model of PREDICTS data, soil organisms in pasture attain similar taxon richness and abundance as in primary vegetation. This agrees with other studies that found high soil fauna biomass in temperate grasslands (Heděnec et al, 2022). Pastoral management practices cause less physical disruption of the soil structure than many arable farming practices (Aksoy et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Greater amount of nematode herbivory reduces the plant biomass in general, and changes the biomass allocation pattern as seen in grasslands ( Brinkman et al., 2015 ; Franco et al., 2020 ). The nematodes also help to shape the vegetation community aboveground ( Hedenec et al., 2022 ). As seen in the coastal dune grasslands, the specialist PPNs play pivotal role in natural succession by bringing the end of dominant plant species followed by the non-host plant establishment ( van der Putten et al., 1993 ).…”
Section: Nematodes As Ecosystem Drivers In the Climate Change Continuummentioning
confidence: 99%
“…mites and collembolas) and macrofauna (e.g. earthworms, isopods and millepedes) are also important contributors to litter decomposition (Anderson 1978;Korboulewskyet al 2016;Heděnec et al 2022). The quality and palatability of plant-derived resources affect soil invertebrate diversity (Cebrian 1999;Kurokawa et al 2010;Bastida et al 2020).…”
Section: Introductionmentioning
confidence: 99%